Mineral and Bone Consequences of High Dose Denosumab Therapy to Treat an Aneurysmal Bone Cyst, a Child Case Report - Del Sindaco, Giulia; Berlanga, Pablo; Brugières, Laurence; Thebault, Eric; Mantovani, Giovanna; Wicart, Philippe; Linglart, Agnès (Frontiers in Endocrinology, 2021)
Aneurysmal bone cysts (ABCs) are rare benign pseudotumoral bone lesions with potential aggressive behavior due to the extensive destruction of surrounding bone. Traditionally, these tumors were treated with open surgery, but there is more and more a shift to less invasive procedures. In particular, treatment for spinal ABCs is generally unsatisfactory due to the risk of morbidity, neurological impairment and recurrence, and there is a need for innovative therapies. Denosumab has been reported as a useful treatment in giant cell tumors of bone (GCTB), so its efficacy has been tested also in other fibro-osseus lesions affecting children and adolescents, such as spinal aneurysmal bone cysts. The pediatric literature is limited to case reports and small series, all of which highlight the efficacy of this treatment on lesions growth and associated bone pain. Some of these reports have already reported well known side effects associated with denosumab, such as hypocalcemia at the beginning of the treatment, and rebound hypercalcemia at the discontinuation. The latter seems to be more frequent in children and adolescents than in adults, probably due to the higher baseline bone turnover in children. In addition, the use of denosumab in young patients could affect both bone modeling and remodeling, even if the consequences on the growing skeleton have not been reported in detail. Here we describe the case of a spinal ABC diagnosed in an 8-year old young boy which was not accessible to surgery but responded favorably to denosumab. Our aim is to describe the rapid changes in mineral and bone homeostasis in this patient, that required advise from the experts of the European Reference Network (ERN) for rare bone and endocrine diseases.